Motivational Factors for Disease Prevention Influencing the COVID - 19 Vaccine Booster Dose Acceptance Services among Elderly Patients with Chronic Diseases Living in the Northeastern Region of Thailand - Intaranongpai, Siranee; Kanedtapilux, Jarawee; Chatsupakul, Jiraporn; Sunipa Motum (Princess of Naradhiwas University Journal, 2025)
Background and Objectives Coronavirus disease 2019 (COVID - 19), which had a high transmission and mortality rate, had become a significant public health and social challenge globally. To mitigate the severity of this issue, COVID - 19 vaccines were developed. In the early stages of the outbreak, the vaccines were designed based on the original strain and administered in a two-dose regimen to stimulate initial immunity. However, breakthrough infections after completing the vaccination series had been frequently observed, primarily due to the decline in immunity over time. As a result, the booster vaccinations were necessitated to continuously enhance immune efficacy. This cross-sectional analytical study aimed to investigate 1) the level of motivation to prevent COVID - 19 and 2) the motivational factors influencing the COVID - 19 vaccine booster dose acceptance services among elderly patients with chronic diseases living in the northeastern region of Thailand. Method The sample group consisted of 441 individuals, selected using stratified random sampling. The research instruments were validated by three experts, with item-objective congruence values ranging from 0.67 to 1.00 and a Cronbach’s alpha reliability coefficient of 0.86. Data were analyzed using descriptive statistics and logistic multiple linear regression. Results It was found that 1) the overall motivational level for preventing COVID - 19 (mean = 4.18, S.D. = .04) was at a high level; 2) the motivational factors influencing the COVID - 19 vaccine booster dose acceptance services among elderly patients with chronic diseases had self-efficacy perception in preventing COVID - 19, which can predict 26.40 % (Beta = 0.36, p-value < .00) Conclusion and Recommendations Based on the results of this study, healthcare personnel involved in COVID - 19 vaccination services can use the findings to plan initiatives that enhance awareness of capabilities among elderly patients with chronic diseases to prevent COVID - 19. This will help elderly patients with chronic disease recognize the necessity and accept the COVID - 19 booster vaccine.